TEACHING SIMPLE PRESENT TENSE BY USING SINGLE SLOT SUBSTITUTION DRILL TECHNIQUE - Vina Eka Pratiwi; Hamdan H. (Jurnal Perspektif Pendidikan, 2017)
The problem of this study was “Is it significantly effective teaching simple present tense by using single slot substitution drill technique to the eighth grade students at Islamic Junior High School Lubuklinggau in the academic year 2015/2016?”The population of this study was 333 students coming from nine classes. The sample was taken through cluster random sampling. The sample of this study was VIII.8 as the sample group with the total number of 35 students. The result was the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that it was significantly effective teaching simple present tense by using single slot substitution drill technique to the eighth grade students Islamic Junior High School Lubuklinggau in the academic year 2015/2016.